Applying Multi-Hour Traffic Assignment to Estimate Trips Distribution between Hours and the Intrinsic Value of Hour of the Day - Haim Aviram (European Regional Science Association (ERSA), 2005)
Recent analysis regarding the patterns and composition of trips in morning peak hour revealed that an increasing part of these trips correspond to non-work related trips. In general, these trips are not specifically associated with morning peak. Other studies show that price elasticity of leisure trips is considerably higher than that of commuting and business trips. According to Wardrop's first principle, if the transportation network maintains equilibrium, then no user could improve his situation by selecting alternative travel route. Expanding on that principle, the fact that non-work related trips (such as shopping, family visits, tourism) take place in the morning peak hour, under congestion conditions, means that the specific hour, not only the duration of time and trip purpose, is important to the user. Hence, each hour of the day has its own intrinsic value, named "Intrinsic Hourly Value” (IHV). In order to estimate this value, calibration of a multi-hour equilibrium assignment is suggested to determine the magnitude and characteristics of the IHV. Several hypotheses have been tested with regard to the IHV. For example, significant positive values were estimated for morning IHV. The methodology was applied using the demand and data from the Haifa Metropolitan Area. Commonly used models were employed for the multi-hour traffic assignment. Consequently, a clear methodology to estimate the IHV is presented. The results can assist public authorities to decide on policies such as activities time rescheduling or the application of congestion tolls.
Keywords: 330